Longer-term and landmark analysis of transcatheter vs. surgical aortic-valve implantation in severe aortic stenosis: a meta-analysis - Wang, Yu; Zhang, Xiaowen; Zhang, Xinlin; Xu, Wei (Frontiers in Cardiovascular Medicine, 2025)
BackgroundPrevious reports of longer-term outcomes of transcatheter aortic valve implantation (TAVI) focus on higher risk patients and suggest potential temporal changes.AimsTo evaluate the longer-term and temporal performances of TAVI compared to surgical aortic valve replacement (SAVR).MethodsRandomized controlled trials reporting outcomes with at least 1-year follow-up. The primary outcome was the composite of all-cause death or disabling stroke.ResultsWe included 8 trials with 8,749 patients. TAVI was associated with a higher risk of longer-term (5-year) primary outcome compared to SAVR among higher-risk [odds ratio (OR), 1.25; 95% CI, 1.07–1.47] but not lower-risk participants [1.0 (0.77–1.29)]. However, a significant temporal interaction was detected in both risk profiles. TAVI with balloon-expandable valves was associated with a higher risk of longer-term primary outcome compared to SAVR [1.38 (1.2–1.6)], whereas no statistical difference was found with self-expanding valves [1.03 (0.89–1.19)]. There was a significant interaction between the two valve systems, and a temporal interaction was detected in both systems. Overall landmark analysis revealed a lower risk in TAVI within the initial 30 days [0.76 (0.6, 0.96)], comparable between 30 days to 2 years [1.04 (0.85, 1.28)], and higher beyond 2 years [1.36 (1.15–1.61)]. Analysis for all-cause death generated largely similar results.ConclusionsTAVI was associated with a higher longer-term risk of primary outcome compared to SAVR in higher-risk patients and with balloon-expandable valves. However, a characteristic temporal interaction was documented in all subgroups. Future studies are warranted to test these findings.